Analisis Kepadatan Lapis Pondasi Kelas A Terhadap Nilai CBR Soaked Pada Jalan Parkir Proyek Rehabilitasi dan Renovasi Stadion Gelora B.J Habibie: Analysis of Class A Base Layer Compaction on Soaked CBR Value In The Parking Road of the Rehabilitation and Renovation Project of Gelora B.J Habibie Stadium - Munadrah; Firman, Risman; Febry Fitriani Sofyan, Yanny; Tamsil Yunus, Ahmad; Satar, Syahrul; Limbongan, Joey; Widiasari Maruddani, Andi (CV Insight Publisher, 2025)
The compaction of the base layer plays a crucial role in enchancing soil bearing capacity for pavement construction. This studi aims to analyze the effect of varying compaction blows on the soaked California Bearing Ratio (CBR) value of Class A base layer in the Rehabilitation and Renovation Project of Gelora BJ.Habibie Stadium. The tests were conducted with three compaction variations: 10,25, and 56 blows. The result indicate that an increase in the number of blows correlates with a higher CBR value, where a CBR of 51,33% was obtained with 10 blows, increasing to 67,37% with 25 blows, and reaching 98,38% with 56blows. These finding confirm that compaction can significantly improve soil bearing capacity and pavement stability.